2021
DOI: 10.1038/s41598-021-84990-4
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of potassium and cadmium on growth, root morphology and chlorophyll a fluorescence in tomato plant

Abstract: A hydroponic experiment was conducted to evaluate the role of potassium (K) in tomato plant growth exposed to cadmium (Cd) stress. In this work, the effects of three potassium nutrition regimes (155, 232 and 310 ppm of K) combined with Cd at different levels (0, 12 and 25 µM of CdCl2) on chlorophyll content index, root and shoot dry weights, root morphology, chlorophyll a fluorescence and translocation factor were analyzed. The results showed a negative effect of cadmium, at different concentrations, on all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Chlorophyll content is an important index for indicating environmental stress in plants and reflects plant tolerance. In addition, chlorophyll content has been considered to be a reliable stress-induced biomarker to assess heavy metal-induced phytotoxicity in a variety of farmland crops 61 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll content is an important index for indicating environmental stress in plants and reflects plant tolerance. In addition, chlorophyll content has been considered to be a reliable stress-induced biomarker to assess heavy metal-induced phytotoxicity in a variety of farmland crops 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Essential nutrients, mainly K, can promote the activity of these enzymes when the crop is under metal stress. K aids in the transportation of water and nutrition via the xylem and may further promote the involvement of many other latent enzymes 61 . Therefore, with the application of slaked lime, supplementing with K increased H 2 O 2 detoxification due to increased SOD and CAT activity 50 .…”
Section: Resultsmentioning
confidence: 99%
“…4A) indicated that this element affected the process involving the trapping of the exciton to the reduction of PQ and those plants could maintain the maximum PQ reduction rate (Adamski et al 2011). VOI ≥ 1 is related to the I-P phase and reveals the changes in the electron flux from the plastoquinol (PQH2) to the end electron acceptors on the PSI acceptor side (Yusuf et al 2010, Braga et al 2020, Naciri et al 2021). The higher amplitudes observed through the normalization between the O-I steps (VOI ≥ 1.0) in Se-treated plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These various biotic and abiotic stresses cause changes in the crop plant by disrupting its balance of reactive oxygen species (ROS). Overproduction of ROS impairs membrane integrity and cellular function by interfering with photosynthesis, mineral absorption, and assimilation ( Naciri et al, 2021 ). To mitigate elevated ROS production and metabolic protection, plants will often upregulate their antioxidant system and accumulate more osmolytes ( Ghani et al, 2019a ; Ahanger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%